On the move to meaningful internet systems. OTM 2017 Conferences : Confederated International Conferences: CoopIS, C & TC, and ODBASE 2017, Rhodes, Greece, October 23-27, 2017, Proceedings /: OTM 2017 Conferences : Confederated International Conferences: CoopIS, C & TC, and ODBASE 2017, Rhodes, Greece, October 23-27, 2017, Proceedings. Part I : (2017) - Unknown
No abstract available